Penggunaan Missouri Mathematics Project (MMP) dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa MAN 1 Jombang - Erviningsih Setyorini; Nur Laili Achadiyah; Abdussakir Abdussakir (ARITHMETIC: Academic Journal of Math, 2022)
This study aims to increase student activity and learning outcomes by using the Missouri Mathematics Project (MMP) learning model on trigonometry equations. This research is a Classroom Action Research conducted in 3 cycles at MAN 1 Jombang. The subjects of this study were 36 students of class XI MIPA 6. The research instruments included observation sheets and achievement tests. Analysis of student activity is carried out using the percentage formula while learning outcomes are carried out by calculating the average test score. The results showed that the percentage of student activity increased in each cycle, namely 61.81%, 73.61%, and 84.72%. The average student learning outcomes have increased in each cycle, namely 67.08, 73.19, and 85.28. The percentage of students who passed experienced an increase in each cycle, namely 50.00%, 66.67%, and 83.33%. It can be concluded that the use of the Missouri Mathematics Project learning model can increase student activity and learning outcomes in trigonometric equations.